Study of the immunological efficacy and safety of a candidate vaccine against Lassa hemorrhagic fever - O. Popova; O. V. Zubkova; T. A. Ozharovskaia; D. I. Zrelkin; D. V. Voronina; P. P. Goldovskaya; V. Yu. Kan; I. V. Dolzhikova; A. V. Kovyrshina; D. M. Grousova; I. A. Ermolova; D. V. Shcheblyakov; et al. (Медицинская иммунология)
Lassa hemorrhagic fever is an acute human infectious disease with high mortality rate and pandemic potential. To date, there are no approved drugs for the specific treatment or prevention of Lassa hemorrhagic fever in the world. The aim of this study was to develop and evaluate the immunobiological properties and preclinical safety of a candidate vaccine for the prevention of Lassa hemorrhagic fever (LHF) based on recombinant human adenoviral vectors. Standard genetic engineering techniques, molecular biology techniques, virological methods, and animal testing procedures were used in the course of the study. A combined vector candidate vaccine for the prevention of Lassa hemorrhagic fever has been designed and characterized. The vaccine is composed of two components for heterologous immunization in a prime-boost regimen. Both components are based on recombinant replication-defective adenovirus vectors. The first component of the vaccine is a recombinant human adenovirus type 26; the second component is a recombinant human adenovirus type 5. Both recombinant vectors contain the codon-optimized sequence of Lassa virus glycoprotein. Two experimental batches of the candidate vaccine were produced under GMP-conditions and analyzed. The results of studies in compliance with appropriate specifications for viral vector vaccines are provided. In preclinical studies in mice, antigen-specific IgG response was detected after immunization with two vaccine components, either separately, or in a prime-boost regimen. The time dynamics of the IgG response was also studied on 42, 77, 119 and 147 days after immunization. At the same time, despite achieving 100% seroconversion, no virus neutralizing antibodies were detected in any of the samples collected from immunized mice. A biodistribution study showed that 24 hours following intramuscular injection of the vaccine components, the DNA of adenovirus vectors was detected only at the site of injection and in regional lymph nodes. Based on preclinical safety assessments (including acute toxicity, chronic toxicity, immunotoxicity, allergenic properties, reproductive toxicity), no contraindications were found for initiation of the candidate Lassa vaccine clinical trials. Taken together, the results demonstrate that the candidate vaccine for prevention of Lassa hemorrhagic fever based on recombinant adenovirus vectors types 26 and 5 is a promising drug for specific immunoprophylaxis.